EXPLORING THE LIVED EXPERIENCES OF SOCIAL WORKERS DEALING WITH DEAF CLIENTS (Proceedings of the International Conference on Social Sciences, 2024)
: Social Workers deal with diverse client including deaf individuals. However, dealing with deaf clients can be challenging, especially for new social workers without much experience with this type of client. The study was conducted to explore the lived experiences of social workers in dealing with deaf clients. It involved four social workers with experience dealing with deaf clients for at least 3 years and working in Cagayan de Oro City. This study employed Creswell's Simplified Version of Moustaka’s adaptation of the Stevick-Colaizzi-Keen Method of Phenomenological Analysis. The data analysis procedure involved bracketing of experience, horizontalizing the data, clustering of meanings, writing a textural description and structural description of the experiences of the participants, and writing the essence of collective experience. Four themes emerged in the study namely; Walking through client behavior; Dealing with client management issues; Employing client-centered strategies; and Providing meaningful services. These identified themes emphasize the complex nature of interactions between social workers and deaf clients. It shows how social workers wok hard to understand and connect with the deaf clients, revealing a potential gap in education and information on effectively addressing this unique client group. The study highlights critical need for specialized training, ongoing professional development, and a deepened cultural competence among social workers engaging with the deaf community. The insights gained from this study pave the way for the enhancement of social work curricula, training programs, and support structures, ensuring that future practitioners are equipped with the skills, insights, and sensitivity required to forge meaningful connections and provide effective, client-centered services.
Keywords: deaf; lived experience; transcendental phenomenology; challanges; strategies